Pulseless Electrical Activity: Echocardiographic Explanation of a Perplexing Phenomenon - Parish, David C.; Goyal, Hemant; James, Erskine; Dane, Francis C. (Frontiers in Cardiovascular Medicine, 2021)
Finding a person with no pulse and consciousness with continued electrocardiographic complexes obviously raises the question of how they got there. Lack of clear understanding of how PEA emerges has limited research into interventions that might improve the low rates of survival typically associated with PEA. Over 30 years of studying and practicing resuscitation has allowed the authors to see a substantial rise in PEA and variable survival among patients in PEA based on their illness spectrum and intensity of monitoring. This paper presents a small prospective observational study of individuals whose family members consented to the observation of the dying process after disconnection from life support following brain death and demonstrates that PEA is a late phase in the clinical dying process. Our echocardiographic findings of the emergence of PEA in 3 patients will offer prospects for further studies on the subject to improve survival.